2015
DOI: 10.1371/journal.pone.0138523
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Real-Time Shear Wave Elastography in the Assessment of Testicular Torsion

Abstract: Real-time shear-wave elastography (SWE) is a newly developed method which can obtain the stiffness of tissues and organs based on tracking of shear wave propagation through a structure. Several studies have demonstrated its potential in the differentiation between diseased and normal tissue in clinical practices, however the applicability to testicular disease has not been well elucidated. We investigated the feasibility and reproducibility of SWE in the detection of testicular torsion. This prospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Therefore, testicular torsion cannot be excluded in patients with normal blood flow signals in CDUS and we should take into account the possibility of a special type of testicular torsion <360°. Shear wave elastography is useful for evaluating testicular torsion 26 and should be examined further in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, testicular torsion cannot be excluded in patients with normal blood flow signals in CDUS and we should take into account the possibility of a special type of testicular torsion <360°. Shear wave elastography is useful for evaluating testicular torsion 26 and should be examined further in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with strain elastography, SWE has the advantages of quantitative evaluation of soft tissue stiffness, strong repeatability and higher clinical application value [15], including testis pathology [16]. The results of clinical and animal experiments showed that the SWE values of testicular parenchyma significantly increase during testicular torsion [17,18]. But it is not clear whether the changes can be distinguished from other scrotum emergencies such as acute orchitis.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been published aiming at investigating the feasibility of SWE for evaluating testicular pathologies, and those studies were limited to neoplastic processes [4][5][6][7], infarction [4,8,9], torsion [10], or orchitis [7], and differentiating between these pathologies [7,11,12]. Testicular elastography investigations in clinical practice were mostly focused on masses.…”
Section: Introductionmentioning
confidence: 99%